Potencial silvicultural de Myracrodruon balansae (Engler) D. A. Santin: espécie em perigo de extinção no sul do Brasil - Barbosa, Felipe Manzoni (2019)
Myracrodruon balansae (Engler) D. A. Santin (pau-ferro-do-sul) belongs to the Anacardiaceae family and is a south Brazil native plant. It has a hard wood (1.1 to 1.25 g.cm- 3) generally applied in rural constructions, firewood, in addition to being a source of extractives and used in folk medicine. In consequence of the past harvest, process the specie has described in the endangered category. Despite the uses and status of conservation, there are few studies on seed technology, seedling production in the nursery and growth in the field. In this sense, this research were divided in three chapters, in Chapter I was carried out the initial characterization of the germination, substrates and evaluation of the physical, physiological and sanitary quality of the diaspores stored in different environments. The batch of diaspores were collected in the city of Unistalda, RS and evaluated for the weight of one thousand seeds, moisture level, germination test and sanity. The diaspores stored in a refrigerator with a moisture content of 10% had their greatest potential for storage for 18 months, with a loss of 20% of the initial germinative potential. In the sanity test the main genus of fungi found in the diaspores were Aspergillus spp. and Penicillium spp. In Chapter II the effect of substrates and fertilizer sources on the morphological and physiological characteristics of M. balansae seedlings was evaluated. For this, four substrates with carbonized rice husk (CAC) and Sphagnum type peat and four fertilizers were formulated. The morphological attributes evaluated were: height (H), collection diameter (DC), H / DC ratio, aerial dry matter (MSA), root dry matter (MSR), total dry matter IQD), root length (CR) and leaf area (AF) and physiological attributes: initial fluorescence (Fo), maximum fluorescence (Fm) and maximum photochemical efficiency of photosystem II (Fv/Fm). The species is responsive to fertilizer sources, the use of 60% of Sphagnum peat plus 40% of CAC and controlled release fertilizer (FLC), 05.05.09 (N-P2O5-K2O), we recommend for production of seedlings with morphological and physiological quality. Chapter III had the objective of evaluating the initial growth and development of M. balansae under different nitrogen rates and the resilience to the occurrence of frost in the initial phase of planting. The treatments used were 0, 50, 100, 200 kg of urea ha-1 with about 45% nitrogen. At 180 days after planting the survival, H and DC and the physiological variables Fo, Fm, Fv/Fm, quantum yield, chlorophyll a, chlorophyll a and carotenoids were evaluated. The survival time was 98% and the growth in height and diameter of the collection at 180 days after planting was 107.0 cm and 15.26 mm, respectively, with the use of about 50 kg of ha-1 urea . At 270 days after planting the plants were damaged by frost, being verified the resilience, H, DC, number and length of shoots. The species shows to be sensitive to frost, but it presents resilience, by means of satisfactory budding in the first year of planting, when nitrogen fertilization was carried out.